Neuroendocrine Liver Metastases and Orthotopic Liver Transplantation: The US Experience - N. Thao T. Nguyen; Theresa R. Harring; John A. Goss; Christine A. O'Mahony (International Journal of Hepatology)
Liver transplantation remains a controversial therapy for Neuroendocrine liver metastases (NLM), with coflicting suvival data reported. The aim was to assess the evolution of outcomes for patients transplanted for NLM in the US, both before and after the introduction of the MELD scoring system in 2002. The UNOS/OPTN database was reviewed to identify patients diagnosed with NLM who subsequently underwent a liver transplantation from 1988 to March 2011 (𝑛=184); Patient survival was determined using Kaplan-Meier methods and log-rank tests, and cox regression analysis was performed, using SPSS 15.0 (SPSS, Inc, Chicago, IL). The overall NLM patient survivals in the pre-MELD era were 79.5%, 61.4%, and 49.2% at 1, 3, and 5 years, respectively. After the introduction of the MELD score, NET/NLM patients had improved overall patient survivals at 1, 3, and 5 years of 84.7%, 65%, and 57.8%. Patients transplanted after 2002 had an improved survival outcome. Notably, the overall patient survival for NET is not significantly different when compared to the outcomes of patients transplanted for HCC, in the current era. This progress acknowleges the significant improvement in outcomes for NLM patients after liver transplantation and the potential for further gain in the survival of otherwise nonsurgical, terminal patients.